Long-term outcomes of refractory Takayasu arteritis patients treated with biologics including ustekinumab. Issue 3 (4th May 2021) - Gon, Yoshie; Yoshifuji, Hajime; Nakajima, Toshiki; Murakami, Kosaku; Nakashima, Ran; Ohmura, Koichiro; Mimori, Tsuneyo; Terao, Chikashi
Abstract: Objectives: Biologics have been used to treat refractory Takayasu arteritis (TAK), but their efficacy and safety have not been sufficiently evaluated. Methods: We extracted clinical information from medical records for TAK patients who were treated with biologics including ustekinumab (UST) at Kyoto University Hospital. We also analysed the patient's genetic backgrounds. Results: Of 163 cases, 12 (7.4%) were treated with infliximab, tocilizumab, or UST (n = 3). Erythrocyte sedimentation rate (ESR), C-reactive protein levels (CRP), and prednisolone (PSL) dose were significantly decreased 12 months after the initiation of biologics. When compared with the 15 patients who were only treated with immunosuppressants (IS group), the change in ESR from baseline was significantly lower in the biologics group than in the IS group (−2 mm/h, p = .005). The proportion of patients with HLA-B*52 and the risk-type alleles of the SNP were similar in both groups. Among the biologics, TCZ showed the highest continuation rate. UST exhibited marginal effects on reducing ESR, CRP levels, and PSL dose. No adverse events were observed in patients with UST for approximately 3 years. Conclusions: Biological treatments resulted in a reduction in inflammatory markers and PSL dose in refractory TAK patients.